Influence of Cenosphere on Compression After Impact Strength of Glass Epoxy Laminates. (22nd December 2021) - Rajendran, Balaji; Kumar P K, Dinesh
Abstract: Under controlled lab settings, two distinct laminates, one containing cenosphere and the other with neat resin, were evaluated for impact strength using a Fractovis impact machine, compression, and Compression After Impact (CAI) strengths through Tinus Olsen UTM. The GFRP laminates were prepared with 16 layers of glass fiber combined with epoxy resin reinforced Cenospheres at concentrations of 1, 3 and 5 wt%, according to ASTM specifications. The dominant failure mode controlling the specimen's compression ultimate load resistance, and other failure modes of impacted specimens such like fiber pull-out and debonding, were found to be the effects of delamination using coupled coustic emission (AE) monitoring and compression tests. On specimens with a 3 wt% filler additive, there was a noticeable increase in strength. Both impacted and non-impacted samples exhibited significant compression ultimate load resistances, with the 3 wt% filler impregnated specimen having the maximum.